O processo de formação e ocupação do Bairro dos Estados em João Pessoa-PB - Lima, Anne Stephanie Oliveira de (2014)
This dissertation examines the formation and the physical growth of Bairro dos Estados, a neighborhood located at João Pessoa, the capital city of Paraíba State, in Brazil, which in the 1970s and 1980s was the most preferred residential area for the local middle and upper class families. It aims at two main objectives: (a) to explain how the lands of the neighborhood were subdivided in order to create the streets, blocks and lots which constitute it today; and (b) to show how the blocks and lots were gradually occupied by buildings. The study that generate it was based mainly on the analysis of varied images – aerial photos, other photos, plans of the city and projects of allotments – and the main method used in it was the comparative one. The situations portrayed by images concerning the years 1976, 1989, 1998 and 2008 were compared. These are some essential facts of the history revealed by the research: the neighborhood had its origin in a street layout approved in the 1920s; part of this layout started to be occupied by houses in the end of the following decade; in the late 1960s only some small stretches of the neighborhood were not yet subdivided into blocks and lots; after 1970 numerous middle and upper class families settled down in the neighborhood, giving it a privileged status; in the late 1980s the neighborhood was already a consolidated urban tissue, with good infrastructure and few vacant lots, but it started to be rivaled by some burgeoning coastal neighborhoods; in the two following decades it experienced a loss of prestige and a certain stagnation; latterly, it regained a certain prestige thanks to the replacement of many of its houses by apartment towers, shops and office buildings. Being the first study on the neighborhood with the approach adopted here, this work aims to give a contribution to the understanding of the physical growth of the capital of Paraiba during the last nine decades.